2016
DOI: 10.18632/oncotarget.9835
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between osteoprotegerin (OPG), fatty acid synthase (FASN) and, cycloxygenase-2 (COX-2) in breast cancer: implications in carcinogenesis

Abstract: The crosstalk between malignant and nonmalignant cells in the tumor microenvironment, as maneuvered by cytokines/chemokines, drives breast cancer progression. In our previous study, we discovered Osteoprotegerin (OPG) as one of the cytokines heavily secreted by breast cancer cells. We demonstrated that OPG is expressed and secreted at very high levels from the highly invasive breast cancer cell lines SUM149PT and SUM1315MO2 as compared to normal human mammary epithelial HMEC cells. OPG was involved in modulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 71 publications
0
33
0
Order By: Relevance
“…32,33 Similarly, we observed upregulated α v β 3 integrin in mPASMCS and PAs, where its interaction with osteoprotegerin induced of FAK and AKT phosphorylation and cell proliferation. Previous studies have also shown that osteoprotegerin secreted by breast cancer cells could interact with fatty acid synthase, 8 which plays a key role in pulmonary vascular remodeling. 34 However, rOPG stimulation induced primary OPG -/-PASMC proliferation independent of fatty acid synthase expression ( Figure VI in the Data Supplement).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32,33 Similarly, we observed upregulated α v β 3 integrin in mPASMCS and PAs, where its interaction with osteoprotegerin induced of FAK and AKT phosphorylation and cell proliferation. Previous studies have also shown that osteoprotegerin secreted by breast cancer cells could interact with fatty acid synthase, 8 which plays a key role in pulmonary vascular remodeling. 34 However, rOPG stimulation induced primary OPG -/-PASMC proliferation independent of fatty acid synthase expression ( Figure VI in the Data Supplement).…”
Section: Discussionmentioning
confidence: 99%
“…6,7 However, recent clinical and experimental data have also linked osteoprotegerin to carcinogenesis and a range of cardiovascular disorders, including PAH. [8][9][10][11] Notably, clinical data showed that osteoprotegerin serum levels were higher in idiopathic pulmonary hypertension and associated with the indicators of disease severity and prognosis, and also indicated that osteoprotegerin expression was increased in both concentric and plexiform lesions in remodeled pulmonary arteries.…”
Section: See Clinical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Those fatty acids can be further modified and used for cellular processes, such as membrane formation and posttranslational protein modification [7,9,10]. The specific FASN inhibitor C75 is effective in inhibiting tumor growth in numerous cancer models [11][12][13]. Whether FASN is important for Th17 effector function in comparison to other CD4 + Th subsets remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that a high level of the inflammatory cytokine IL-6 has been associated with increased tumor stage, lymph node infiltration, recurrence, and treatment resistance [34]. Several cytokines regulate the inflammatory tumor microenvironment, of which CRP, IL-6, and TNF-α stimulate cancer cell proliferation and invasion [35]. Our results indicate that patients following breast cancer surgery in the 7 days postoperatively experienced elevated serological levels of CRP, IL-6, and TNF-α than before operation.…”
Section: Discussionmentioning
confidence: 99%